2005
DOI: 10.22358/jafs/70710/2005
|View full text |Cite
|
Sign up to set email alerts
|

Response of broiler chickens to <i>Lactobacillus</i> and <i>Bifidobacterium</i> probiotic strains

Abstract: The effects of two Lactobacillus and two Bifidobacterium probiotic strains (given daily in an amount of 10 9-10 10 live cells per bird, in water) as well as an antibiotic, avilamycin (8 mg/kg of diet), were determined. The live body weight of chickens in groups receiving probiotics or avilamycin (2625-2665 g) was higher than in the control group (2564 g), however the differences were not significant. The feed conversion ratio was significantly better in most of the investigated groups in comparison with the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…This is in agreement with the avilamycin-fed chickens showing partially decreased immune factors mediating the killing of pathogens, which is in contrast to the enhancement of immune response caused by probiotics. However, in our previous work [6], the average live body weight of 39-day-old chickens fed with avilamycin (2,655 g) or with the same probiotic strains as employed in the current work under similar conditions (from 2,625 g in the L. acidophilus group to 2,665 g in the B. animalis group) did not differ significantly and was slightly higher when compared to the controls (2,564 g). Thus, different levels of immune defense markers and acute-phase reaction, considered as an immunological stress in our model and, therefore, possibly influencing catabolic activities, did not seem to affect the body weight of the treated chickens.…”
Section: Discussionmentioning
confidence: 43%
See 4 more Smart Citations
“…This is in agreement with the avilamycin-fed chickens showing partially decreased immune factors mediating the killing of pathogens, which is in contrast to the enhancement of immune response caused by probiotics. However, in our previous work [6], the average live body weight of 39-day-old chickens fed with avilamycin (2,655 g) or with the same probiotic strains as employed in the current work under similar conditions (from 2,625 g in the L. acidophilus group to 2,665 g in the B. animalis group) did not differ significantly and was slightly higher when compared to the controls (2,564 g). Thus, different levels of immune defense markers and acute-phase reaction, considered as an immunological stress in our model and, therefore, possibly influencing catabolic activities, did not seem to affect the body weight of the treated chickens.…”
Section: Discussionmentioning
confidence: 43%
“…We monitored the augmentation of ceruloplasmin content as a marker of acute-phase response and compared the effect of the feed additives on a large number of chickens (280) over a period of 6 weeks. We employed the chicken-animal model to continue the work of previous studies that demonstrated the growth-promoting effect of probiotics-the probiotics-fed and antibiotics-fed chickens did not show a significant difference in body weight [6]. We also showed the in vitro reduction in Salmonella by the probiotics strains [6,11] used in the current work.…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations